Inhibitors of tumor necrosis factor (TNF) in sarcoidosis:Who,What, and How to use them - Baughman, R.P.; Lower, E.F.; Drent, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Sarcoidosis patients with chronic disease often require prolonged treatment. Although alternatives to corticosteroids have been frequently administered in this disease, corticosteroids remain the mainstay of treatment. However disabling side effects which accompany prolonged treatment can necessitate the use of alternative, steroid-sparing agents. The tumor necrosis factor (TNF) inhibitors can be useful in treating chronic sarcoidosis. Among the biologic agents which inhibit TNF, infliximab has been studied most extensively in sarcoidosis with fewer reports available for adalimumab and etanercept. This review will summarize the available evidence to identify the best candidate to receive an anti-TNF regimen as well as the relative benefits and side effects of the three anti-TNF biological agents for treating sarcoidosis. A stepwise approach is proposed to increase the likelihood of disease improvement for patients who experience an inadequate response to an anti-TNF agent.